Oxidative Stress and Cardiorespiratory Function - Pokorski, Mieczysław (Advances in experimental medicine and biology, 2015)
Cardiorespiratory function is prominently affected by oxidative stress. Cigarette smoking is the archetype of oxidative and nitrative stress and free radical formation. New adverse effects of smoking keep on propping up in research. The chapters provide the comprehensive view of new developments in this area regarding cardiovascular and lung function and muscle catabolism. Alterations in inflammatory cytokines and proteins as well as degradation of muscle proteins due to smoking, by far unrecognized, caused by oxidative stress also are presented. Much less is known about the effect of cognitive stress on vagally-mediated cardiorespiratory function and surprisingly, on vagal immune pathway. The experimental studies also show that clinically important meconium aspiration syndrome contains an oxidative trait which is amenable to antioxidative treatment. This volume creates a source of information on the damaging role of oxidative stress in cardiorespiratory function that has by far not been available